ADDITIONAL SPAN OF SPACE FRAME ANALYSIS AND ALTERNATIVE DESIGN USING CABLE STRUCTURE ON WEST-EAST GRANDSTAND OF GELORA BANDUNG LAUTAN API - Oktaviane Vikarani, Ghea
Gelora Bandung Lautan Api is a stadium which is equipped with space frame roof. The roof which has been built doesn’t cover the entire grandstand, so the demand to increase roof spans is appear. Existing strucutre could not hold the load due to the addition of roof span so it has to be analyzed. If the analysis shows that the existing structure isn’t strong enough, one solution is to add a cable structure. Cable structure is a structural system that utilizes steel cable as load bearing elements. Cable structure used for suspension bridge, including a buffer for long-span roof. The basic principle of the cable structure is to engineer the structure shape so that the overall load will be modified to tensile load. Compared to other structure, cable structure is different because it’s nonlinear behavior. Disanvantage from this system is weak resistance to corrosion and vibration, especially wind. This weakness caused by it’s nature of the steel cable that doesn’t have compression stiffness. This weakness can be resolved by pretension methode.